The Effect of Financial Literacy and Financial Inclusion on the Use of Fintech (Paylater) by Shopee Paylater Users - Devi Oktavia Azahra; Hidayatul Khusnah (Jurnal Akuntansi, 2026)
This study aims to analyze the influence of financial literacy and financial inclusion on the use of Shopee Paylater Fintech services in students of Nahdlatul Ulama University Surabaya. The approach used is quantitative with a survey method through the distribution of questionnaires to 101 respondents selected by purposive sampling. The data were analyzed using multiple linear regression with the help of SPSS software version 25. The results of the study show that financial literacy does not have a significant effect on the use of Shopee Paylater, while financial inclusion has a positive and significant effect on the use of the service. These findings show that student access and involvement in formal financial services is a dominant factor in driving the use of Fintech. This research is expected to contribute to academic and practical understanding of the financial behavior of the younger generation in the digital era.